(untitled) (Research, Society and Development, 2021)
Pigmented lesions of the oral mucosa comprise a diverse group of lesions that can range from physiological pigmentations, such as gingival pigmentation in people with black skin, to severe pathological pigmentations, such as oral melanoma. The identification of pigmented tissue in the oral cavity can represent difficulties in the diagnosis for the health professional. This occurs because the clinical manifestations of pigmented lesions are diverse and can vary from focal to diffuse macular coloration, or even from a small nodular growth to a large mass. Given the above, this study aimed to review the literature on pigmented lesions of the oral mucosa, highlighting their clinical presentation, diagnosis and treatment, as well as the importance of corrective clinical management in patients who have such lesions in the oral cavity. For the construction of this work, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, using the Mendeley reference manager. Scientific studies available in the literature report that there are several pigmented lesions that affect the oral mucosa. These complications involve amalgam tattooing, oral melanotic macula, melanocytic nevus, melanoma, and oral melanoacanthoma. Therefore, it is extremely important that health professionals are familiar with these lesions, distinguishing them from malignant lesions that affect the oral cavity, in order to establish the correct treatment for each case.